2010
DOI: 10.1189/jlb.0609432
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in a mouse model of histiocytosis: transformation of Langerin+ dendritic cells, macrophages, and precursors

Abstract: Neoplastic diseases of macrophages (M phi) and dendritic cells (DC), collectively called histiocytoses, are relatively rare. The etiology of most forms of histiocytosis is poorly understood, and the development of animal models is crucial for further research in this field. Previously, an animal model for malignant histiocytosis (MH), involving transformed histiocytic cells, has been generated by infecting mice with malignant histiocytosis sarcoma virus (MHSV). However, increased insight into the heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Moreover, improved molecular diagnostics have indicated that many cases diagnosed earlier as malignant histiocytosis appeared to represent either anaplastic large cell lymphoma, involving malignant lymphocytes that show a histiocyte‐like appearance, or malignancies of dendritic cell origin (86, 87). Thus, the reappraisal of malignant histiocytosis as a human disease as well as the recently increased awareness of the heterogeneity of the dendritic cell lineage inspired us to re‐evaluate the identity of the cells transformed in the MHSV mouse model (88).…”
Section: Are Lch Cells Intrinsically Aberrant?mentioning
confidence: 99%
“…Moreover, improved molecular diagnostics have indicated that many cases diagnosed earlier as malignant histiocytosis appeared to represent either anaplastic large cell lymphoma, involving malignant lymphocytes that show a histiocyte‐like appearance, or malignancies of dendritic cell origin (86, 87). Thus, the reappraisal of malignant histiocytosis as a human disease as well as the recently increased awareness of the heterogeneity of the dendritic cell lineage inspired us to re‐evaluate the identity of the cells transformed in the MHSV mouse model (88).…”
Section: Are Lch Cells Intrinsically Aberrant?mentioning
confidence: 99%
“…34,37 A previous model of histiocytosis was generated by infecting mice with malignant histiocytosis sarcoma virus, leading to transitional macrophages/DC sarcomas. 38 Another experimental model was induced by transgenic expression of the SV40 T oncogene in DCs. 39 These mice developed infiltration of spleen, liver, bone marrow, thymus, and mesenteric lymph node with CD11c þ CD8 þ CD207 þ DCs, resembling the aggressive form of LCH.…”
Section: Discussionmentioning
confidence: 99%